A utilisation analysis of antimicrobial drugs in the Intensive Care Unit of the Johannesburg Hospital. - Rodopouls, George (My University, 2014)
A three month study to evaluate costs associated with the utilisation of antimicrobial drugs was undertaken in the Intensive Care Unit of the Johannesburg hospital. A total of 62 patients were entered in the study. Coagulase-negative Staphylococcus was found to be the most prominent bacterial pathogen (53%) followed by Acinetobucter bauma?mii (30.6%). Candida albicans was the most prominent yeast (53%). The study identified the use of catheters and mechanical ventilation as putative risk factors for the acquisition of infection in the ICU. The most frequently prescribed antimicrobial drug was gentamycin (21.7%). The acquisition cost of antimicrobial drugs was R 115 793.51 whilst the cost associated with the use of disposables for antimicrobial drug administration was R 15 075.67. Wastage costs were estimated to be R 3800. The total antimicrobial drug cost was therefore estimated to be R 134 669.18 ( i.e. R 2172.08 per patient). Five patients received inappropriate antimicrobial drug therapy. The cost of alternative treatment would have resulted in cost savings of not less than R 827.62. The information from this drug utilisation study helps to assess the current practice of antimicrobial use in the ICU setting and assists in developing future protocols which will optimise the allocation of available resources.